Intransitive encounter : Sino-U.S. literatures and the limits of exchange - Da, Nan Z. (Columbia University Press, 2018)
"In Intransitive Encounter, Nan Da argues that the transnational readings of literary and cultural exchanges often read too much into their significance or mistake the nature of that interaction. The push to characterize these exchanges as developing a cosmopolitanism or producing elements of cultural imperialism misses the particularities or limits of cross-cultural interactions. Taking a closer look at a series of encounters among Chinese and American writers, scholars, and activists during the nineteenth century, Nan Da considers how ideas from other cultures were actually thought about and used in ways to preserve their own national traditions or in ways quite different than their original intent. The book is structured around different episodes of exchange that includes such figures as Washington Irving, Emerson, Yung Wing (founder of the Chinese Educational Mission at Yale), Longfellow, and Chinese and American feminist writers at the end of the century"--